SHARP Joint Action – Strengthening International Health Regulations and preparedness in the EU - Katz, A (Eur J Public Health, 2020)
Although the preparedness to health emergencies of biological, chemical, environmental and unknown origin across the Europe is at high level, gaps do exist across the EU Member States and European countries. The previous coronavirus epidemic, SARS in 2002, showed that countries responded largely individually to this emerging threat. EU wide, joint responses were not taken. SARS epidemic showed that strengthening of the common EU efforts was needed. Many actions were taken, and since 2013 the European Commission Decision 1082/2013/EU on serious cross-border threats to health has provided a framework to improve preparedness and to strengthen the response capacities in Europe to health threats. SHARP Joint Action is a 3-year collaborative action of 26 countries and 61 partners, co-funded by the EC and coordinated by the Finnish Institute for Health and Welfare, Finland, and co-coordinated by Robert Koch Institute, Germany and National Institute of Infectious Diseases Lazzaro Spallanzani, Italy. SHARP started it's actions in June 2019, and it aims to strengthen implementation of the International Health Regulations (IHR) and the Decision 1082/2013/EU. SHARP consists of ten work packages covering core public health capacities, including: IHR core capacity strengthening and assessment, preparedness and response planning, training, laboratory preparedness and responsiveness, chemical safety and threats, and case management, infection prevention and control preparedness. Through this cross-sectoral approach, SHARP supports the Member States and partner countries in strengthening their capacities. In response to the COVID-19 outbreak, SHARP has also supported the EC and the Member States, and especially work packages for laboratory preparedness and responsiveness (WP7) and for case management and infection prevention and control preparedness (WP10) were activated. The activities regarding laboratory preparedness and response have been coordinated with the ECDC. KEY MESSAGES: SHARP Joint Action strengthens the implementation of Decision 1082/2013/EU on serious cross-border threats to health and the implementation of International Health Regulations in the EU. SHARP improves preparedness and response to serious cross-border threats to health, and resilience of the health systems at national, EU and regional level.